1988
DOI: 10.1111/j.1600-051x.1988.tb02125.x
|View full text |Cite
|
Sign up to set email alerts
|

Forced eruption combined with gingival fiberotomy

Abstract: A new approach to clinical crown lengthening has been developed and described. The technique combines controlled eruptive tooth movement and incision of the supracrestal gingival attachment. The procedure was performed in patients with severe destruction of a tooth crown and in whom clinical crown lengthening procedures were essential before the teeth could be properly restored. Controlled eruptive forces were activated by simple orthodontic appliances. During the active phase of forced eruption, repeated intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 13 publications
0
31
0
2
Order By: Relevance
“…Gingival recession represent the most common side effect of this procedure, and it is evident especially in patients with a thin thickness of buccal bone [24]. Kozlovsky et al [25] suggested the adding of root planning to supracrestal fiberotomy every two weeks in order to decrease the attachment of fibers on the root. Traditionally, forced extrusions have been performed alone or in combination with surgical procedures for clinical crown lengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Gingival recession represent the most common side effect of this procedure, and it is evident especially in patients with a thin thickness of buccal bone [24]. Kozlovsky et al [25] suggested the adding of root planning to supracrestal fiberotomy every two weeks in order to decrease the attachment of fibers on the root. Traditionally, forced extrusions have been performed alone or in combination with surgical procedures for clinical crown lengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Ingber (2) managed soft tissue cosmetic deformities using orthodontic extrusion, but orthodontic extrusion can reverse the osseous architecture around the tooth being extruded. Kozlovsky et al (6) described an orthodontic extrusion technique associated with CSF that prevented coronal migration of bone tissue and gingival tissue. Furthermore, Berglundh et al (5) demonstrated that repeated fiberotomy led to pronounced recession of the gingival margin and extensive loss of the connective tissue attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in cases where movement of bone margin and attachment along with the tooth is not desirable (as in crown-root fractures), there is a need for periodical circumferential supracrestal fiberotomy at the start and every 2 weeks during orthodontic extrusion [35]. According to experimental studies and clinical reports, orthodontic extrusion of teeth with one or two wall-infrabony defects results in a more favorable position of the connective tissue attachment and reduction in the defect [36][37].…”
Section: Orthodontic Treatment As An Adjunct To Periodontal Therapymentioning
confidence: 99%